The impact of transvaginal, mesh-augmented level one apical repair on anorectal dysfunction due to pelvic organ prolapse - Wenk, Maren; Göttl, K.; Witczak, M.; Yassouridis, Alexander; Gold, D. M.; Liedl, Bernhard (International urogynecology journal, 2022)
Introduction and hypothesis: The objective was to investigate the symptom prevalence of anorectal dysfunction (AD) in women with pelvic organ prolapse (POP) and whether symptom improvement can be achieved by pelvic floor surgery. Methods: Secondary analysis of the Propel Study data from 277 women with POP stage II–IV regarding bothersome AD symptoms, which were assessed using the Pelvic Floor Distress Inventory (PFDI) questionnaire preoperatively, and 6, 12, and 24 months after transvaginal prolapse repair with Elevate anterior and posterior. Results: Prevalence of AD was high in the study cohort (14.4–56.3%) and could be reduced significantly throughout a 2-year follow-up (cure rates 44.3–83.1%). AD symptoms decreased in a similar manner after posterior/apical fixation to the way they did after anterior/apical fixation (e.g., feeling of incomplete bowel emptying 66.7% to 25.5% vs 46.5% to 10.7% respectively). Hemorrhoids and loss of loose stool decreased even more after anterior/apical fixation than after posterior/apical fixation. Even though AD symptoms decreased significantly more in patients with POP stage III–IV, there was still a considerable improvement in patients with POP stage II (e.g., pain when passing stool 31.1 to 7.7% vs 21.4 to 0% respectively). Notably, even symptoms of hemorrhoids and rectal prolapse improved substantially (cure rates 44.2% and 70.1% respectively). Conclusions: Symptoms of AD were frequent in our study cohort, and they significantly improved after vaginal mesh-augmented sacrospinous prolapse repair with Elevate anterior and posterior throughout the follow-up period. Anterior/apical fixation showed results that were almost as good as those after posterior/apical fixation. Patients with POP stage II experienced considerable symptom improvement, but cure rates were significantly higher in patients with POP stage III–IV.